PECULIARITIES SECRETION OF HOMOCYSTEINE AT YOUNG WOMEN WITH POLYCYSTIC OVARY SYNDROME - Архипкіна, Т.Л. (World of Medicine and Biology, 2014)
Polycystic ovary syndrome (PCOS) is associated with hyperandrogenism, abdominal obesity, dyslipidemia, hyperinsulinemia, insulin resistance. The investigators assumed that the high levels of homocysteine are as the result by metabolic disorders, hyperandrogenism and leads to endothelial dysfunction, high levels of endotelin-1. There are disputable data of the increased concentration of homocysteine in serum at women with PCOS in the scientific literature. OBJECTIVE. To determine the levels of homocysteine at young women with PCOS and estimate the relationship of homocysteine and hormonal parameters, metabolic parameters and levels of endothelin-1.METHODS. We examined 65 patients (age 26.1±0.2 years) with PCOS and 15 healthy women with a normal menstrual function. All patients with PCOS were divided into two groups: first group – 45 women with a normal body mass index (21,4±0,3 kg/m2), second group – 20 women with obesity (28,8±0,7 kg/m2). The basal levels of total testosterone (T), estradiol (E2), endothelin-1, homocysteine, insulin and index HOMA were investigated at all women.RESULT(S).The results indicate that 51.5% women with PCOS have high levels of homocysteine (103.7±0.4 mmol / l) in the blood serum.It was established that the frequency of hyperhomocysteinemia in patients with PCOS, independent of body weight (χ2 = 1.2; p> 0.05), HOMA index (χ2 = 0.07; p> 0.05), insulin levels (χ2 = 1.07; p>0.05), T levels (χ2 = 1.23; p>0.05), E2 levels (χ2 = 0.96; p>0.05).It has been proved that the content of ET-1 in the serum of young women with PCOS (2,29 ± 0,2 fmol/ml) is much higher than the average healthy women (0,83±0,2 fmol/ml; p>0.05). It has been found that the frequency of the of high level of ET-1 at women with PCOS with presence of hyperhomocysteinemia is increas than at patients with normal level of homocysteine. The results indicate that hyperhomocysteinemia is an independent risk factor for the formation of endothelial dysfunction and may contribute to remote complications of the disease.Screening of hyperhomocysteinemia at a young age can be a useful indicator of hidden disorders of endothelial function and diseases of the reproductive system.
Keywords: polycystic ovary syndrome; homocysteine; endothelin-1